p300-Mediated Lysine 2-Hydroxyisobutyrylation Regulates Glycolysis - Huang, He (Mol Cell, 2018)
Lysine 2-hydroxyisobutyrylation (Khib) is an evolutionarily conserved and widespread histone mark like lysine acetylation (Kac). Here we report that p300 functions as a lysine 2-hyroxyisobutyryltransferase to regulate glycolysis in response to nutritional cues. We discovered that p300 differentially regulates the Khib and Kac on distinct lysine sites, with only 6 out of the 149 p300-targeted Khib sites overlapping with the 693 p300-targeted Kac sites. We demonstrated that diverse cellular proteins, particularly glycolytic enzymes, are targeted by p300 for Khib but not for Kac. Specifically, deletion of p300 significantly reduces Khib levels on several p300-dependent, Khib-specific sites on key glycolytic enzymes including ENO1, decreasing their catalytic activities. Consequently, p300 deficient cells have impaired glycolysis and are hypersensitive to glucose depletion-induced cell death. Our study reveals a p300-catalyzed, Khib-specific molecular mechanism that regulates cellular glucose metabolism, and further indicate that p300 has an intrinsic ability to select short-chain acyl-CoA-dependent protein substrates.